Specific Inhibition of DNMT3A/ISGF3γ Interaction Increases the Temozolomide Efficiency to Reduce Tumor Growth - Cheray, Mathilde (Theranostics, 2016)
DNA methylation is a fundamental feature of genomes and is a candidate for pharmacological manipulation that might have important therapeutic advantage. Thus, DNA methyltransferases (DNMTs) appear to be ideal targets for drug intervention. By focusing on interactions existing between DNMT3A and DNMT3A-binding protein (D3A-BP), our work identifies the DNMT3A/ISGF3γ interaction such as a biomarker whose the presence level is associated with a poor survival prognosis and with a poor prognosis of response to the conventional chemotherapeutic treatment of glioblastoma multiforme (radiation plus temozolomide). Our data also demonstrates that the disruption of DNMT3A/ISGF3γ interactions increases the efficiency of chemotherapeutic treatment on established tumors in mice. Thus, our data opens a promising and innovative alternative to the development of specific DNMT inhibitors.